Cosmopolitanism and Global Ethics. (February 2017) - Zhang, Longxi
Embracing all humanity as one's own is the core of the modern idea of cosmopolitanism, but the present time with rising tribalism, populism, racism, and narrow-minded nationalism is not propitious for cosmopolitanism. At a time like this, the cosmopolitan effort to see cultures and peoples as close to one another rather than absolutely different becomes all the more important. The comparative study of different cultures and literatures may promote a cosmopolitan stance, and from a comparative perspective, we may draw some ideas from the ancient Chinese philosopher Mencius for a theory of global ethics. *